Effect of heart rate control with amiodarone infusion on hemodynamic and clinical outcomes in septic shock patients with tachycardia: a prospective, single-arm clinical study - Masoud Khataminia; Farhad Najmeddin; Atabak Najafi; Hamidreza Sharifnia; Arezoo Ahmadi; Adeleh Sahebnasagh; Mojtaba Mojtahedzadeh (BMC, 2021)
Abstract Background Keeping the heart rate within the normal range has improved the survival of septic shock patients. Amiodarone could target the underlying pathophysiology of sepsis-induced tachycardia. This study aimed to determine whether amiodarone is effective in controlling the heart rate in critically ill patients with septic shock and sustained tachycardia who were receiving vasopressor. Methods In this prospective, single-arm cohort study, 46 patients with septic shock and tachycardia were enrolled to receive a loading dose of amiodarone 150 mg, then continuous infusion of 1 mg/min. The primary outcome was the ability of amiodarone in rate control lower than 95 beats per minute (BPM) and maintaining it during 24-h study period. We also recorded the effect of amiodarone on hemodynamic indices as the secondary outcomes. Results The results of the present study indicated a significant decrease in HR in septic shock patients for amiodarone, from 121.0 (116.5, 140.0) at baseline to 91.5(89.3, 108.0) at the end of the study period (p < 0.001). During the study period, a total of 26 (56.52%) of patients achieved the target heart rate lower than 95 BPM and maintained it during study period. Amiodarone decreased HR by 22.8 ± 13.7. While receiving amiodarone infusion, the values for heart rate, mean arterial pressure, cardiac index, norepinephrine infusion rate, and stroke volume index changed significantly between amiodarone initiation and 24-h follow-up (P < 0.001). Amiodarone was well tolerated, because this anti-arrhythmic agent did not increase the need for vasopressor and none of the patients experienced episodes of refractory hypotension. Conclusion This study showed that amiodarone infusion successfully reduced the heart rate in sepsis-induced tachycardia. The patients had improved hemodynamic state as indicated by an increase in cardiac index and SVI.